The Analysis of Critical Thinking Ability and Self-Effacement Toward Carousel Feedback Learning Model - Nathalia Yohana Johannes; Elsinora Mahananingtyas (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2021)
This research is aimed to find out the presence of causality by analyzing students’ critical thinking ability in applying Carousel feedback learning model. This research employed quasi experimental research. The subject of the study was the fifth grade students of elementary1 and 4 Naira. There were 39 students. The instrument of the research was essay test that used to test the cognitive aspect with the purpose to measure the result of students’ conceptual mastery in their critical thinking ability. Besides test, there were two questionnaires that used in order to get information about students’ response toward the implementation of Carousel feedback learning k,model and the second questionnaire was used to analyze students’ self-efficacy. The result of critical thinking ability with nonparametric test and the Wilcoxon test showed that there was significance 0.000 < 0.05. Therefore, Ho was rejected and H1 was accepted. This means that there were differences in students' critical thinking skills before and after the implementation of Carousel Feedback learning model. Moreover, the result of students’ self-efficacy showed that the result of paired sample test was significance 0.016 < 0.05. Thus, it was decided that Ho was rejected and H1 was accepted. It can be said that there was difference about the ability of students’ self-efficacy before and after implementing Carousel feedback model in learning.